Cultural Roots of Parenting: Mothers’ Parental Social Cognitions and Practices From Western US and Shanghai/China - He, Huihua; Usami, Satoshi; Rikimaru, Yuuki; Jiang, Lu (Frontiers in Psychology, 2021)
Cultural values can be considered as important factors that impact parents’ social cognitions and parenting practices. However, few studies compare specific cultural values of parents and the relationships between cultural values and parenting processes in eastern and western contexts. This study examined the ethnicity differences in mothers’ cultural values, parental social cognitions (child-rearing ideologies and goals) and parenting practices between Mainland Chinese and European American contexts. Predictors of parenting goals and parenting practices were also investigated. Mothers of 4-6 years old children from Western US (N = 78) and Shanghai/China (N = 96) participated in this study. The results suggested that mothers from Shanghai/China were both more collectivistic and individualistic than mothers from Western US. Chinese mothers more strongly endorsed in training and collectivistic parenting goals, while European American mothers more strongly endorsed individualistic parenting goals for their children. However, no significant difference was found in parenting practices for both groups of mothers. For both ethnic groups, in general, mothers’ cultural values have small but significant impact on their parenting processes. The prediction of cultural values and parenting goals on parenting practices were also different for both ethnicity groups. Although Chinese mothers were higher on both individualism and collectivism, their collectivistic values were more important in predicting parental social cognitions.